The SECI model of knowledge creation as an enabler of students’ creative behavior through the lens of absorptive capacity - Han, Lifen; Zhao, Yanwu (Frontiers in Psychology, 2026)
IntroductionThe present study investigates how the SECI model of knowledge creation enables students’ creative behavior through absorptive capacity pathways.MethodsDrawing on data from 395 university students in China collected across three waves, the research applies partial least squares structural equation modeling (PLS-SEM) to examine both lower-order and higher-order representations of SECI.ResultsThe results show that SECI significantly enhances acquisition, assimilation, and transformation, confirming its predictive role in absorptive capacity development. In addition, mediation analysis reveals that acquisition and transformation serve as significant pathways linking SECI to students’ creative behavior, while assimilation, although positively predicted by SECI, does not directly foster creativity.DiscussionThese findings contribute to absorptive capacity theory by clarifying the relative strength of its pathways and extend the SECI framework by validating it as a higher-order construct in educational contexts. Beyond theoretical contributions, the study highlights practical implications for higher education institutions: fostering environments that emphasize knowledge acquisition and transformation, alongside integrated SECI processes, can enhance students’ creative competencies.